Enhanced Information System Security in Internet Banking and Manufacturing (International Journal of Engineering Materials and Manufacture, 2020)
The internet has contributed significantly by changing how we interact with other people and how we execute business today. By virtue of the internet, electronic commerce has emerged, facilitating business to manage their customers and other corporations inside more effectively and outside their industries. The industry which is applying business transaction using this new communication channel to reach its customers is the banking industry. The electronic banking system addresses several emerging trends such as customer's demand for anytime, anywhere service, product time-to-market imperatives and increasingly complex back-office integration challenges. The challenges that oppose electronic banking are concerns of security and privacy of information. This paper will first discuss the current forms of security threats in the internet banking; secondly, it will investigate weaknesses in the current information security protocols of the internet banking. Thirdly, it will propose an enhanced information system security for internet banking.